The effect of market risk on the expected credit losses computed in accordance with International Financial Reporting Standard (9)(An Analytical study on conventional banks listed on the Damascus Securities Exchange) (Damascus University Journal for the economic and Political sciences, 2025)
The research aims to study the impact of market risks on expected credit losses in accordance with International Financial Reporting Standard No. (9) within the traditional banks listed on the Damascus Securities Exchange, based on financial statements published during the quarterly financial periods from March 31, 2020 to March 31, 2022.The descriptive and analytical approach followed in this paper using a sample of (11) banks represent the conventional banks listed on the Damascus securities exchange.The paper concluded that there is a significant positive impact of market risks on the expected credit losses for conventional banks listed on the Damascus Stock Exchange during the period studied.
Keywords: Market Risks (MR); Expected Credit Losses (ECL)